The surgery of the alimentary tract - Devine, Hugh (John Wright & Sons, 1940)
The Surgery of the Alimentary Tract provides information pertinent to the fundamental aspects of the surgery of the alimentary canal and its adnexal organs. This book examines the selection of operative methods, improvements in the operative method, and the advantages of pre-operative and post-operative treatment. Organized into four parts encompassing 93 chapters, this book begins with an overview of the sites of obstruction in the esophagus. This text then discusses the general symptoms of dyspepsia, including discomfort, pain, heartburn, flatulence, acid eructation, nausea, vomiting, and vi.